1988
DOI: 10.1128/jvi.62.5.1730-1735.1988
|View full text |Cite
|
Sign up to set email alerts
|

DNA rearrangements in organ-specific variants of polyomavirus JC strain GS

Abstract: Variants of JC virus (JCV) strain GS were isolated directly from the central nervous system (variant GS/B) and the kidney (variant GS/K) of a patient with progressive multifocal leukoencephalopathy and were cloned and sequenced. The genomes of the isolates were shown to be nearly identical in the nucleotide sequences of their protein-coding regions, suggesting that both had originated from a single infecting JCV genome. In contrast, the arrangement of the putative elements of transcriptional control revealed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(63 citation statements)
references
References 32 publications
(31 reference statements)
1
62
0
Order By: Relevance
“…This search led to the discovery of the archetype regulatory region. Derived from virus in kidney tissue [82,96,97] and urine [60,[62][63][64][65][66][67][68]74], archetype singularly contained all the nucleotide elements found in repeat structures. The limited biological activity of the archetype regulatory region, however, led to debate concerning the roles of JCV variants in PML pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This search led to the discovery of the archetype regulatory region. Derived from virus in kidney tissue [82,96,97] and urine [60,[62][63][64][65][66][67][68]74], archetype singularly contained all the nucleotide elements found in repeat structures. The limited biological activity of the archetype regulatory region, however, led to debate concerning the roles of JCV variants in PML pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CY had a 66-bp insert after nucleotide number 91 that contained sequence comprising almost every downstream insertion seen in repeat structures [81]. Variant GS/K, isolated 2 years earlier in Germany from a PML patient whose kidneys harbored JCV [82], was nearly identical to CY, except for a single base pair deletion in the 66-bp insert. Viruria observed in most populations contained JCV with nucleotide structure similar to the CY and GS/K variants [81,[83][84][85][86][87][88][89].…”
Section: Jcv Genomic Variantsmentioning
confidence: 99%
“…The JC virus was found to target intranuclear domains called PML-NBs. 15,[18][19][20] Because PML happens to also be the abbreviation for "promyelocytic leukemia", to avoid confusion in this review, the PML abbreviation is used only to refer to progressive multifocal leukoencephalopathy, while "promyelocytic leukemia" is abbreviated in combination with "nuclear bodies" as PML-NBs. PML-NBs are ubiquitously present in mammalian cells and are associated with a variety of nuclear functions, including DNA repair, transcription, cell cycling, apoptosis, senescence and others.…”
Section: New Neuropathological Findings: Dot-shaped Inclusionsmentioning
confidence: 99%
“…12,13 The Tokyo-1 strain was the first virus isolated in Japan and one of the three major isolates in the world, together with Mad-1 in the United States and GS/B in Germany. 14,15 In 1984, Tokyo-1 was inoculated in golden hamsters, and brain tumor, medulloblastoma was induced. 16 In 1987, the regulatory sequence of Tokyo-1 was characterized, and its unique 17-bp insertion in the regulatory region was identified.…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanism and site of this rearrangement are unknown, however a similar process may occur in a second human polyomavirus, JC virus (JCV), where it has been suggested that an archetype form undergoes active replication and TCR rearrangement at the site of primary infection [Newman and Frisque, 1997]. The emergent rearranged variants may then be transported to different tissues where they may become established based on their tissue-tropic properties [Martin et al, 1985;Loeber and Dörries, 1988;Newman and Frisque, 1999].…”
Section: Introductionmentioning
confidence: 99%